2018
DOI: 10.1001/jamacardio.2018.3466
|View full text |Cite
|
Sign up to set email alerts
|

Association of Weather With Day-to-Day Incidence of Myocardial Infarction

Abstract: IMPORTANCE Whether certain weather conditions modulate the onset of myocardial infarction (MI) is of great interest to clinicians because it could be used to prevent MIs as well as guide allocation of health care resources. OBJECTIVE To determine if weather is associated with day-today incidence of MI. DESIGN, SETTING, AND PARTICIPANTS In this prospective, population-based and nationwide setting, daily weather data from the Swedish Meteorological and Hydrological Institute were extracted for all MIs reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 43 publications
2
67
2
6
Order By: Relevance
“…A direct comparison of our study finding with previous studies is difficult owing to the differences and inconsistencies in the study design and statistical methods. On an aggregate level, we observed the same relationship between temperature and AMI, along with with the same seasonal variations, as the studies conducted in the past [5,[9][10][11][12][13][14][18][19][20]. Among other metrological variables, temperature variations have a profound and consistent impact on the incidence of AMI, not only in its extreme states (both high and low) but also transient change in temperature can trigger acute myocardial infarction (AMI) [5].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A direct comparison of our study finding with previous studies is difficult owing to the differences and inconsistencies in the study design and statistical methods. On an aggregate level, we observed the same relationship between temperature and AMI, along with with the same seasonal variations, as the studies conducted in the past [5,[9][10][11][12][13][14][18][19][20]. Among other metrological variables, temperature variations have a profound and consistent impact on the incidence of AMI, not only in its extreme states (both high and low) but also transient change in temperature can trigger acute myocardial infarction (AMI) [5].…”
Section: Discussionsupporting
confidence: 76%
“…Among other metrological variables, temperature variations have a profound and consistent impact on the incidence of AMI, not only in its extreme states (both high and low) but also transient change in temperature can trigger acute myocardial infarction (AMI) [5]. The potential biological mechanism behind temperature variation-triggered AMI was explained as coronary plaque instability and myocardial ischemia precipitated by increased blood pressure and heart rate due to subsequent vasoconstriction after a rise in catecholamine levels due to the stimulation of cold receptors in the skin [18,[21][22][23][24]. Furthermore, exposure to the cold temperature causes haemoconcentration and a decrease in plasma volume and an increase in diuresis and blood viscosity, which can result in increased platelet counts and plasma concentration which may stimulate thrombosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Boussoussou et al have reported positive significant association between acute cardiovascular diseases and a cold front effect lagged by one day [14]. Mohammad et al demonstrated that incidence of myocardial infarction increased with higher wind velocity, lower air temperature, lower atmospheric air pressure, and shorter sunshine duration [15]. Similarly, Honda et al found that increased incidence of acute myocardial infarction corresponds to lower minimum temperature occurring on the second day preceding the onset of wind [17].…”
Section: Introductionmentioning
confidence: 98%
“…A large body of evidence reported in the literature shows there is an association between windrelated environmental variables and cardiovascular or cerebrovascular events, with impact observed also on the preceding days [14][15][16][17][18][19][20][21][22][23]. Boussoussou et al have reported positive significant association between acute cardiovascular diseases and a cold front effect lagged by one day [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ergebnis Von den 1076 identifizierten Patienten verstarben 66 % außerhalb und 34 % während ihres Krankenhausaufenthaltes. Die innerhalb und außerhalb der Kliniken am Infarkt Verstorbenen zeigten keine Unterschiede im Anteil Frauen (40,4 % innerhalb, 39,0 % außerhalb; p = 0,671), in der Häufigkeit der Obduktion (16,(8)(9)(10)(11)(12)(13)(14)(15)(16)6 %; p = 0,938) oder in der Todesart "nicht natürlich" bzw. ungewiss (17,(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)3 %; p = 0,388).…”
unclassified